2006
DOI: 10.1002/we.204
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis for wind turbines

Abstract: Modern wind turbines are complex aerodynamic, mechanical and electrical machines incorporating sophisticated control systems. Wind turbines have been erected in increasing numbers in Europe, the USA and elsewhere. In Europe, Germany and Denmark have played a particularly prominent part in developing the technology, and both countries have installed large numbers of turbines. This article is concerned with understanding the historic reliability of modern wind turbines. The prime objective of the work is to extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
271
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(276 citation statements)
references
References 3 publications
4
271
0
1
Order By: Relevance
“…This is clearly illustrated by Another study, concerning Danish and German wind power plants [10], shows the same tendency. Indeed, principal contributors to the higher German failure rate are the electrical control or system subassemblies (grid or electrical system, yaw system and mechanical or pitch control system) rather than mechanical subassemblies such as the gearbox.…”
Section: Failure Mode Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…This is clearly illustrated by Another study, concerning Danish and German wind power plants [10], shows the same tendency. Indeed, principal contributors to the higher German failure rate are the electrical control or system subassemblies (grid or electrical system, yaw system and mechanical or pitch control system) rather than mechanical subassemblies such as the gearbox.…”
Section: Failure Mode Analysissupporting
confidence: 58%
“…Real wind turbine failure data quantitative analyses have shown important features of failure rate values and trends [8][9][10][11]. For illustration, Fig.…”
Section: Failure Mode Analysismentioning
confidence: 99%
“…Danish data shows a decreasing number of installed turbines, while German wind turbines increase rapidly [9] [10] . Since the population changes, it's necessary to eliminate the population difference by normalizing the wind turbine reliabilities.…”
Section: Windstats Datamentioning
confidence: 99%
“…concluded that fewer authors have worked on reliability evaluation of wind turbine systems [8] . Valuable information for wind turbine reliability analysis can be derived from failure data by statistical analysis [9] [10] . Climate change can also be taken into account using statistical data [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Current studies of wind turbines focus on improving reliability [4,9,10] because good wind turbine reliability, together with predictable turbine maintenance schedule, will result in a reduced cost of energy, which will determine the success of a wind farm project. This is even more important for offshore wind farms due to their high initial capital cost and limited accessibility, causing higher operational and maintenance (O&M) cost [11,14] and prolonged capital payback.…”
Section: Introductionmentioning
confidence: 99%